Intestinal Damage in COVID-19: SARS-CoV-2 Infection and Intestinal Thrombosis - Wu, Xiaoming; Jing, Haijiao; Wang, Chengyue; Wang, Yufeng; Zuo, Nan; Jiang, Tao; Novakovic, Valerie A.; Shi, Jialan (Frontiers in Microbiology, 2022)
Intestinal tract, with high expression of ACE2, is one of the major sites of extrapulmonary infection in COVID-19. During pulmonary infection, the virus enters the bloodstream forms viremia, which infects and damages extrapulmonary organ. Meanwhile, uncontrolled viral infection induces cytokine storm and promotes a hypercoagulable state, leading to systemic microthrombi. Both viral infection and microthrombi can damage the gut-blood barrier, resulting in malabsorption, malnutrition and intestinal flora entering the blood, ultimately increasing disease severity and mortality. Early prophylactic antithrombotic therapy can prevent these damages, thereby reducing mortality. In this review, we discuss the effects of SARS-CoV-2 infection and intestinal thrombosis on intestinal injury and disease severity, as well as the corresponding treatment strategies.